2012 Fourth International Workshop on Quality of Multimedia Experience 2012
DOI: 10.1109/qomex.2012.6263866
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in crowd-based video quality assessment

Abstract: Video quality evaluation with subjective testing is both time consuming and expensive. A promising new approach to traditional testing is the so-called crowdsourcing, moving the testing effort into the Internet. The advantages of this approach are not only the access to a larger and more diverse pool of test subjects, but also the significant reduction of the financial burden. Recent contributions have also shown that crowd-based video quality assessment can deliver results comparable to traditional testing in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…The migration to crowdsourcing invokes some conceptual challenges on how to assess QoE and how to design the user tests [29]. In laboratory studies user tests may take up to 90 minutes [30] which allow, for example, to investigate memory effects [31].…”
Section: B Conceptual Challenges For Qoe Crowdtestingmentioning
confidence: 99%
“…The migration to crowdsourcing invokes some conceptual challenges on how to assess QoE and how to design the user tests [29]. In laboratory studies user tests may take up to 90 minutes [30] which allow, for example, to investigate memory effects [31].…”
Section: B Conceptual Challenges For Qoe Crowdtestingmentioning
confidence: 99%
“…Also, in Table 2 the row "λ" depicts the λ values for each model, used in Eq. (2). From the provided results of these tables we can see that LASSO is a sparser approach compared to OLS.…”
mentioning
confidence: 79%
“…First studies by Keimel et al [140,141] have shown that crowdtesting can indeed provide results similar to the results from formal subjective testing in a laboratory environment. But as also discussed by Keimel et al [138], many challenges still remain before crowdtesting is a universally acceptable replacement for formal subjective testing.…”
Section: Roommentioning
confidence: 99%